PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - GILANG PRASETYO SUGI, FEBRIANTO Gilang Prasetyo (Jurnal Akuntansi AKUNESA, 2013)
The aimed of this research is to analyze whether company’s characteristic affect to the disclosure of corporate social responsibility. In this research, company’s characteristic is consist of company’s size, company’s profitability and public ownership. Based of this research is the phenomenon of the differences of corporate social responsibility disclosure in Indonesia. There is an inconsistency in many result of research that had been occured. Each of researcher has many different perception in determine which are affected in Corporate Social Responsibility Disclosure. The object of this research are food and beverages companies which are listed in Indonesia Stock Exchange. The result of this research shows that all of the company’s characteristic has positive effect on corporate social responsibility disclosure. Keywords : Company’s Size, Company’s profitability, Public Ownership, Corporate Social Responsibility Disclosure